PENGARUH KUALITAS PELAYANAN DAN CITRA TOKO TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO MERTA SARI DI KOTA DENPASAR - Marjiana Kusuma, I Gede Dedek; Suasana, I Gst. A. Kt. Gd. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.06.TAHUN.2022, 2022)
Micro-enterprises in economic development in Indonesia are sectors that have an important role. This study aims to determine the effect of partial and simultaneous service quality, and image on purchasing decisions. The research was conducted at Merta Sari Store located at Jalan Gunung Tangkuban Prahu No. 7A, Denpasar, Bali. The research respondents were Merta Sari shop customers with a sample size of 90 people. The sampling technique in this study used accidental sampling and data collection techniques in this study used interviews and questionnaires. The research data were analyzed using multiple linear regression analysis techniques. Research can be seen that: service quality has a significant positive effect on purchasing decisions, image has a significant positive effect on purchasing decisions, simultaneously service quality and image have a significant positive effect on purchasing decisions. Suggestions that can be given by researchers is that Merta Sari Store should provide guidance to employees and supervise employees at work. Merta Sari store always provides a fast and precise response to customer complaints and conducts promotions that are even more optimal.